Perceptions and attitudes towards nutrigenomics and their association with the knowledge of genetics among health science undergraduate students in Malaysia - Ng, Yie Enn (2023)
Nutrigenomics serves as the primary principle for developing personalized nutrition plans aimed at preventing and managing diseases. However, a significant number of healthcare professionals currently face a deficiency in the essential knowledge and training required in this field. The restricted familiarity with genetics and genomics may impede their ability to provide advice to patients or effectively utilize the test outcomes. Therefore, it is imperative to equip health science undergraduates with comprehensive education in genetics and nutrigenomics, as they represent the future allied health professionals. This study aimed to determine the perceptions and attitudes towards nutrigenomics and their association with knowledge of genetics among health science undergraduate students in Malaysia. A cross-sectional study was conducted among 423 health science undergraduates by using a self-administered online questionnaire. Subjects were recruited by the convenience sampling method. The results showed that there was a significant difference in genetics knowledge scores among participants with different major programs (p = 0.001), years of iii study (p < 0.001), and prior awareness of nutrigenomics (p < 0.001). Dietetics students (p = 0.020) and Biomedical Science students (p = 0.026) had significantly higher genetics knowledge score than Chinese Medicine students. Year two and Year three students showed a significantly higher knowledge score than Year one students as well (p< 0.001), and attitudes practice variables (p < 0.001). To increase the application of nutrigenomics in medical settings, the positive perceptions and attitudes towards nutrigenomics should be promoted. This can be achieved by reinforcing the genetics education in health science undergraduate programs